Correlation between skeletal development and maxillary canine eruption - Ruba J Mohammad (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to find a correlation between the permanent maxillary canine eruption and the cervical vertebral maturation index (CVMI). Materials and Methods: 145 subjects (73 male and 72 female) in the age of 7-14 years were examined radiographically with lateral cephalographs and orthopantomographs. The CVM patterns were evaluated on the lateral cephalograph using the classification of Hassel and Farman. The stage of the permanent maxillary canine eruption has been investigated on the orthopantomographs depending on its vertical height in relation to the adjacent incisor. Descriptive statistics were obtained for both CVMI stages and canine eruption grading. Spearman rank correlation test was used to determine the correlation between both methods. The minimum level of significance was considered less than 0.05 (P < 0.05). Results: Results showed a strong correlation between CVMI and the grading of the maxillary canine eruption in both female and male and the (r) value estimated was 0.862 and 0.758, respectively. Over 90% of deceleration stage of CVMI in both genders show canine eruption (pubertal growth spurt) about 91.66% for female and 95.65% for male and a small percentage of delay eruption 8.33% and 4.35% in female and male gender, respectively, with a predilection to the female gender. Conclusions: A significant correlation between the permanent maxillary canine eruption stages and skeletal maturity was found. The eruption of maxillary canine occurs before the end of pubertal growth. Any delay in the eruption of maxillary canine after the deceleration stage of CVMI, suggesting a chance of impaction.